Review of the Utilization of Palm Oil Revenue Sharing Funds for Fiscal Year 2024 on the Resilience of the Sei Dadap District, Asahan Regency - Ardi Nugroho; Abdi Sugiarto; Cut Nuraini (Yayasan Sinergi Multidimensi Kreatif, 2025)
This study aims to examine the Review of the Utilization of Palm Oil Revenue Sharing Funds for the 2024 FiscalYear on the Resilience of the Sei Dadap District, Asahan Regency. This research approach is qualitative, aimingto gain an in-depth understanding of the use of Palm Oil Revenue Sharing Fund (DBH) for the 2024 Fiscal Yearon regional resilience in Sei Dadap District, Asahan Regency. The location of the research was carried out in SeiDadap District, Asahan Regency. Qualitative research data collection techniques rely on field data throughinteractive methods that allow direct interaction with data sources. Research Results To increase theeffectiveness of DBH utilization, it is recommended that efforts be made to increase transparency, strengthencommunity participation in decision-making, and increase the capacity of human resources. Continuousmonitoring and evaluation are also important to ensure that the use of funds is in accordance with the needs andexpectations of the community. Thus, the utilization of the Palm Oil Revenue Sharing Fund in Sei Dadap Districtnot only focuses on improving the economy, but also has a wide impact on social resilience and infrastructure,all of which contribute to the sustainable development of the region. Synergistic efforts between the government,the community, and the private sector are needed to continue to improve the results of DBH utilization forcommunity welfare and better regional resilience in the future.